2017
DOI: 10.1016/j.enpol.2016.11.024
|View full text |Cite
|
Sign up to set email alerts
|

Integrated North Sea grids: The costs, the benefits and their distribution between countries

Abstract: A large number of offshore wind farms and interconnectors are expected to be constructed in the North Sea region over the coming decades, creating substantial opportunities for the deployment of integrated network solutions. Creating interconnected offshore grids that combine cross-border links and connections of offshore plants to shore offers multiple economic and environmental advantages for Europe's energy system. However, despite the growing consensus among key stakeholders that integrated solutions can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 3 publications
1
46
1
Order By: Relevance
“…To understand the impact of interconnection on wind integration in the UK, we investigate higher wind capacities in the UK and Nordic countries in separate scenarios with and without interconnection. In contrast with most of the reviewed studies [6,7], our findings suggest that a higher wind penetration in the UK has a negative impact on the socio-economic gain of the NSL link compared to the case of the link operating under today's conditions.…”
Section: The Social Welfare Impact Of the Line Under High Levels Ocontrasting
confidence: 99%
See 1 more Smart Citation
“…To understand the impact of interconnection on wind integration in the UK, we investigate higher wind capacities in the UK and Nordic countries in separate scenarios with and without interconnection. In contrast with most of the reviewed studies [6,7], our findings suggest that a higher wind penetration in the UK has a negative impact on the socio-economic gain of the NSL link compared to the case of the link operating under today's conditions.…”
Section: The Social Welfare Impact Of the Line Under High Levels Ocontrasting
confidence: 99%
“…The planning and preparation phase of the project was completed by 2017 and NSL will interlink the two markets for the first time by 2021. The impact of UK-Nordic interconnectors on power prices in the UK [6], on social welfare gain [7], and on wind integration [8] has proved to be positive for the UK. Despite the Brexit Lockwood et al [9] argues that the UK should pursue the planned interconnections to reduce the costs and losses.…”
Section: Introductionmentioning
confidence: 99%
“…The same results were found in North Seas Countries' Offshore Grid Initiative () when comparing meshed typologies with radial ones, where the authors identified increasing benefits of an integrated NSOG with increasing shares of VRES. Similar findings have also been supported by Strbac, Moreno, Konstantelos, Pudjianto, and Aunedi () and more recently by Konstantelos et al ().…”
Section: Discussionsupporting
confidence: 85%
“…In light of previous studies (Konstantelos et al, ; North Seas Countries' Offshore Grid Initiative, ; Strbac et al, ), it is clear that increasing levels of grid integration yields multiple benefits. The PLI can be viewed as the ultimate level of integration due to its relative high capacity.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, several existing and planned transmission lines are located in the region. Consequently, a meshed offshore grid in the North Sea has been proposed as an option for connecting transmission and offshore wind generation investments in the region (Konstantelos, et al, 2017), (Gorenstein Dedecca, Hakvoort, & Herder, 2017), (De Decker, et al, 2011). This paper presents results from comparing such integrated approach to a project-based scenario, where each offshore wind power plant (OWPP) is connected individually to onshore.…”
Section: Introductionmentioning
confidence: 99%